Prevalência de sífilis em pacientes com HIV/AIDS atendidos em serviço de atendimento especializado em Vitória, ES - Callegari, Fabíola Mesquita (2011)
Backgraound: Syphilis increases the risk of transmitting or contracting HIV and may have change its course in the patients. Reported cases of syphilis among patients living with HIV/AIDS has increased in the last decade, especially among men who have sex with men. Objectives: To determine the prevalence of and factors associated with syphilis infection in HIV/AIDS outpatient clinic at the Santa Casa de Misericórdia de Vitória Hospital, ES. Methods: Cross-sectional study conducted in HIV/AIDS patients treated between August 2010 to September 2011. Patients were interviewed containing demographic , behavioural and clinical signs. Venous blood for VDRL and treponemal test (rapid test) were performed. The prevalence of syphilis was estimated by the presence of positive non-treponemal tests and positive treponemal test and calculated the corresponding confidence interval of 95%. It was applied chi-square test with Yates correction or Fischer and multivariated logistic regression. Results: A total of 438 patients were included in the study. The mean age was (SD 11) years of schooling and 8.1 (SD 4.2) years of study, 55% were men and 26.9% were married or had steady partners. The prevalence of syphilis was 5.3% (CI 95% 3.3% 7.3%). The treponemal test was positive in 18.9% of participants. In multivariated analysis, syphilis was associated with male sex [OR 4,57 CI 95% 1.03-20], being MSM [OR=1,78(IC95% 1,64-4,14)], not using antiretroviral therapy [OR 0,18 CI 95% 0.06-0.59] and previous history of syphilis [OR 5.54 CI 95% 1.95-15.76]. Conclusion: Co-infection of syphilis in patients living HIV/AIDS in customer services to AIDS was 5.3% and was associated with male gender, being men who have sex with men, not use the antiretroviral therapy and previous history of syphilis.